Peer Counselor Communication Style In Increasing UMY Students’ Awareness Of Mental Health - Suciati; Putri Devi Lianda; Ronayunita Audhi (SHS Web of Conferences)
Peer counselors’ communication style towards clients plays an important role in the success of increasing students’ mental awareness. Therefore, this research will discuss peer communication styles with clients as UMY’s efforts to promote awareness regarding mental health. This research aims to determine the communication style of peer counselors to clients at UMY in improving students’ mental well-being. This type of research is descriptive qualitative with data collection techniques of in-depth interviews with six of peer counselors and clients. The data analysis technique is carried out using interactive analysis, where interaction occurs between data collection, data presentation, and conclusion. In this research, it was found that six peer counselors had different communication styles to convey messages to each client, namely cartoon communication; open and leave a message; relaxed, friendly, and attentive. The application of this communication style is influenced by factors that arise from the start to the end of the counseling session. The communication style of peer counselors in higher education, especially UMY, has never been examined in previous research. So, it is hoped that the presence of this research can become a reference for creating a higher education environment that supports students’ overall mental well-being.